Morphological Characterization and DNA Barcoding of Lutjanus agennes (African Red Snapper) from Escravos and Qua Iboe Estuaries - Ewhuwhe-Ezo, John; Eriegha, Ochuko Joshua; Eyo, Victor Oscar (International Journal of Maritime and Interdisciplinary Research, 2024)
Estuaries, as vital nursery grounds for marine species, are vulnerable to over-exploitation and environmental degradation. In this study, the morphological and genetic diversity of Lutjanus agennes (African red snapper) populations from the Escravos and Qua Iboe estuaries in Nigeria were evaluated. A total of 200 fish samples, comprising 100 randomly selected specimens from each estuary, were collected, and detailed morphometric measurements, including total length, standard length, body depth, and fin dimensions, were recorded. Muscle tissues were also collected for DNA barcoding analysis. Notably, fish from the Qua Iboe estuary were significantly larger, with an average total length of 36.91 ± 2.76 cm, compared to 32.12 ± 2.38 cm in the Escravos population. DNA barcoding, utilizing the cytochrome c oxidase subunit I (COI) gene, confirmed species identity. The results of the Basic Local Alignment Search Tool (BLAST) showed a percentage identity ranging from 95.25% to 100% and sequence lengths between 619 and 646 base pairs. These findings revealed minimal genetic divergence between the populations, consistent with the low genetic variation typically observed in estuarine fish due to gene flow facilitated by migration. Although genetically connected, the populations may experience different ecological pressures, as indicated by the larger body size of fish in the Qua Iboe estuary. This research highlights the utility of DNA barcoding for accurate species identification and emphasizes the importance of incorporating genetic and morphometric data into fisheries management to ensure the sustainable exploitation of L. agennes in Nigeria’s estuarine ecosystems.
Keywords: Lutjanus agennes; Morphological diversity; Genetic diversity; Estuarine ecosystems; Fisheries management.